Association between depressive symptoms of mothers and eating behaviors of school-going children in Urban Bangladesh: A cross-sectional study - Sharmin Sultana; Faisal Muhammad; ABM Alauddin Chowdhury; Tasmia Tasnim; Md. Imdadul Haque; Abul Hasan BakiBillah; Md. Kamrul Hossain; Sanjana Zaman; Mohammad Delwer Hossain Hawlader; Moniruddin Chowdhury (BMC, 2023)
Abstract Objective This study aimed to investigate the association between depressive symptoms among mothers and the eating behaviors of their school-going children in Urban Bangladesh. Materials and methods This analytical cross-sectional study was conducted in the context of the urban area of Bangladesh. A multistage sampling technique was applied to select 324 children's mothers in Dhaka City. Data were collected from both city corporation settings in Dhaka, Bangladesh. Semi-structured questionnaires were used in this study. We estimated the depressive symptoms among mothers using the Zung Self-Rating Depression Scale. We examined the association of mothers of school-going children's socio-demographic variables and eating behaviors of school-going children with their mother's depression by using chi-square and evaluating the impact of these variables on mothers' depression through univariate and multivariate binary logistic regression. Results In our study, 57.7% of the mothers of school-going children had depressive symptoms, and 42.3% had no depressive symptoms. The study explored that consuming fewer vegetables (AOR = 0.237, 95% CI: 0.099-0.569), taking fewer fruits (AOR = 0.177, 95% CI: 0.093-0.337), and interestingly, taking fast food less than 4 days per week (AOR = 3.024, 95% CI: 1.517-6.031) were significantly associated with mothers' depressive symptoms. Conclusion Mothers with depressive symptoms of school-going children in Dhaka city are alarmingly high as a grave concern. The eating behaviors of children are associated with their mothers' depressive symptoms. With an aim to build rigorous awareness on depression and child's healthy eating behaviors, it is imperative to arrange health education and awareness related programs.